Rhetorical Transformations in Multimodal Advertising Texts: From General to Local Degree Zero - Rossolatos, George (HERMES - Journal of Language and Communication in Business, 2013)
The use of rhetoric in advertising research has been steadily gaining momentum since the 1980’s. Coupled with an increased interest in multimodality and the multiple interactions among verbal, pictorial and auditory registers, as structural components of an ad filmic text, the hermeneutic tools furnished by traditional rhetoric have been expanded and elaborated. This paper addresses the fundamental question of how ad filmic texts assume signification from a multimodal rhetorical point of view, by engaging in a fruitful dialogue with various research streams within the wider semiotic discipline and consumer research. By critically addressing the context of analysis of a multimodal ad text in the course of the argumentation deployed by different approaches, such as Social Semiotics (Kress/Leeuwen 2001), Film Semiotics (i.e. Metz 1982, Carroll 1980, Branigan 1982), Visual Semiotics (i.e. Sonesson 2008; 2010, Eco 1972;1976;1986, Groupe " 1992), Consumer Research (i.e. Mick/McQuarrie 1999; 2004, Philips 2003, Scott 1994), the relative merits of a structuralist approach that prioritizes the distinction between local and general degree zero, as put forward by Groupe " (1992), are highlighted. Furthermore, the modes whereby rhetorical transformations are enacted are outlined, with view to deepening the conceptual tackling of degree zero of signification, while addressing its applicability to branding discourse and multimodal ad texts.